Erratum: MAOD determined in a single supramaximal test: A study on the reliability and effects of supramaximal intensities - Zagatto, A. M. [UNESP]; Bertuzzi, R.; Miyagi, W. E. [UNESP]; Padulo, J.; Papoti, M. (Thieme, 2016)
The affiliation of Professor Johnny Padulo has been changed. A. M. Zagatto1, R. Bertuzzi2, W. E. Miyagi1, 3, J. Padulo4, 6, M. Papoti5 4 University eCampus, Novedrate (CO), Italy 6 Faculty of Kinesiology, University of Split, Split, Croatia.